A Decade of Global and Local Brand Research: A Systematic Literature Review by Using SLR PRISMA - Fitriana, Ana (MultiTech Publisher, 2024)
This systematic literature review aims to synthesize the evolving research on global and local brand dynamics over the past decade using the PRISMA methodology. It examines the shift from a simplistic global-local dichotomy to a more nuanced understanding of how these brand types interact with consumer identities, digital platforms, sustainability, and global crises. The study explores the emergence of